2010
DOI: 10.2174/2212798411002010061
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Isolation and Analysis of Chondroitin Sulfate Glycosaminoglycans

Abstract: Glycosaminoglycans (GAGs) including chondroitin sulfate (CS) and chondroitin sulfate/dermatan sulfate (CS/DS) copolymers are anionic straight chain polysaccharides. They are galactosamine containing GAGs (galactosaminoglycans) having wide range of applications in pharmaceutical, cosmetic and food industries. This article reviews techniques to isolate and characterize these galactosaminoglycans from animal and poultry tissues. Patent based information is also discussed. Cartilaginous tissues are the major sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…However, in the present study after electrophoresis the gel was visualised by staining with coomassie brilliant blue. Nakano et al ( 2010 ) studied the extraction, isolation and analysis of CS glycosaminoglycan and determined CS molecular mass by polyacrylamide gel electrophoresis and also reported that the mobility of CS was depending on its charge density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study after electrophoresis the gel was visualised by staining with coomassie brilliant blue. Nakano et al ( 2010 ) studied the extraction, isolation and analysis of CS glycosaminoglycan and determined CS molecular mass by polyacrylamide gel electrophoresis and also reported that the mobility of CS was depending on its charge density.…”
Section: Resultsmentioning
confidence: 99%
“…There was no significant difference in CS electrophoresis pattern extracted from different sources. However, Nakano et al ( 2010 ) reported that PAGE has been used to estimate molecular mass of glucosaminoglycans but, it is not much sensitive to detect it’s presence in small variation in the molecular mass, and the results of electrophoresis of CS samples had shown similar migration pattern of standard CS. This indicates that non CS proteins are effectively removed during the extraction process.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this work was to determine the effect of high pressure, temperature and incubation time on the catalytic activity of papain for extracting CS as a potential antioxidant agent. GAGs can be directly extracted from tissues by hydrolysis with exogenous enzymes like papain or pronase [20]. Further separation of the CS in the crude extract was obtained by column chromatography, and the hyaluronic acid binding ability of CS was also examined.…”
Section: Introductionmentioning
confidence: 99%